Transition metal, azide, and oxidant-free homo- and heterocoupling of ambiphilic tosylhydrazones to the regioselective triazoles and pyrazoles - Panda, Subhankar; Maity, Pradip; Manna, Debasis (Organic Letters, 2017)
With N-tosylhydrazone as an ambiphilic reagent, an unprecedented cyclization reaction of two identical or different tosylhydrazones has been developed to access various 4,5-disubstituted-2H-triazoles under transition metal, azide, and oxidant-free conditions. A mechanistic.rationalization study led to the identification of several electronically diverse unsaturated systems for regioselective synthesis of 1- and 2-substituted 1,2,3-triazoles and pyrazoles.